Pengaruh Gaya Hidup, Produk dan Harga Terhadap Keputusan Pembelian Pakian Bekas Pada Konsumen di Kabupaten Pulau Morotai - Umar, Ardin; Siyauta, Irwan (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to determine the effect of lifestyle, product and price on purchasing decisions for used clothing in Morotai Island Regency and is intended to determine how much influence between these variables. Consumers who buy used clothes will act as a research population. While the sample used was 50 respondents. The tests carried out are instrument testing, data testing and hypothesis testing. The research data collection technique was carried out through a questionnaire. Then the analysis of the data obtained in the form of quantitative analysis includes validity and reliability tests, classical assumption tests, multiple regression analysis, regression coefficient tests (R2), F tests and t tests. The results of the t test research show that variable X1 lifestyle has a positive effect on purchasing decisions for used clothing, variable X2 products have no positive effect on purchasing decisions for used clothing, and variable X3 prices on purchasing decisions for used clothing have a positive effect and the results of the f test research or simultaneously obtained that lifestyle, product and price have a significant effect on purchasing decisions for used clothing in Morotai Island Regency.